Implementasi Media Pembelajaran Seni Kriya dengan Seni Tari dalam Pembelajaran Seni Budaya (International Forum of Researchers and Lecturers, 2025)
Arts and Culture learning at the junior high school level requires learning media that can integrate various branches of art in an integrated, contextual, and meaningful manner. One alternative that can be implemented is the integration of craft learning media with dance. This study aims to examine the implementation of the use of craft learning media integrated with dance in Arts and Culture learning at the junior high school level. The approach used in this study is descriptive qualitative with the research location in one junior high school. Data collection was carried out through observation, interviews, and documentation techniques. The results of the study indicate that the application of craft learning media combined with dance, such as making simple dance props and costumes, can increase students' learning motivation, creativity, and understanding of the relationship between the branches of art. The integration of learning media also provides a more contextual and meaningful learning experience. The findings of this study indicate that the development of integrated learning media needs to be continuously optimized to improve the quality of Arts and Culture learning.